Partially isolated four port converter with combined PWM and secondary phase shift control - G. Ranipriya; R. Jegatheesan; K. Vijayakumar (Institute of Advanced Engineering and Science, 2021)
A partially isolated four-port converter is proposed in this paper for interfacing two renewable sources and a storage device with an isolated load. This converter is capable of achieving high power density because of the effective sharing of devices among the input ports. Combined PWM and secondary phase shift control is employed to have a decoupled power flow management of input and output side ports. PWM control is used at the input side for maximum power tracking of renewable sources and battery power management. At the output side, secondary Phase shift control is used for controlling the output voltage. The adopted secondary phase shift control allows the primary switching legs to be operated with 1800 phase shift which results in reduced current ripple at input ports. The working principle of the converter, its output characteristics and control strategy are discussed. Working of the converter and its control strategy is verified through simulation for different input and output conditions. Further, to validate the simulation results, the experimental results of a 500W prototype are also provided.